Ethical Marketing in Orthodontics: A Review - Sumita Mishra1, Ananya Panda2, Smruti B. Nanda3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Due to rise in the Orthodontic treatment by general dental practitioners and pedodontists, there has beena widespread increase in the mass promotion and publicizing by the Orthodontists about their specialtyand particular expertise. Earlier, treatments were advocated in the form of maintenance of good oralhealth, however, it is now being recommended to patients as life-enhancing. Commercialism in publicizingorthodontic care has taken up the field. Because of the elective nature of Orthodontics, highly productivemarketing strategies are aimed at those with discretionary income or insurance benefits. This kind ofcommercialism deteriorates the name and fame of the Orthodontist and the opinion of the people by castinga picture of greed. Inappropriate advertising can make a dental practitioner look more like a business personthan a professional service provider.